2019
DOI: 10.1128/jvi.02151-18
|View full text |Cite
|
Sign up to set email alerts
|

US3 Kinase-Mediated Phosphorylation of Tegument Protein VP8 Plays a Critical Role in the Cellular Localization of VP8 and Its Effect on the Lipid Metabolism of Bovine Herpesvirus 1-Infected Cells

Abstract: Bovine herpesvirus 1 (BoHV-1) infects bovine species, causing respiratory infections, genital disorders and abortions. VP8 is the most abundant tegument protein of BoHV-1 and is critical for virus replication in cattle. In this study, the cellular transport of VP8 in BoHV-1-infected cells and its ability to alter the cellular lipid metabolism were investigated. A viral kinase, US3, was found to be involved in regulating these processes. In the early stages of infection VP8 was localized in the nucleus. Subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…In the early events of virus replication, UL47 protein depends on its RNA binding domain incorporated in one of the UL47 NLSs to bind and potentially transport mRNA ( Donnelly et al, 2007 ), or promotes the transition from α to β and γ genes’ mRNA synthesis ( Shu et al, 2013b ), or regulates viral DNA encapsidation and ND10 redistribution in the nucleus ( Zhang et al, 2015 , 2016 ). Afterward, UL47 protein is translocated to the cytoplasm and accumulated in the Golgi apparatus to be allowed virion incorporation during the late stages of infection ( Zhang et al, 2016 , 2019 ), which is important for UL47 as a major structural protein. During the translocation of UL47 protein from the nucleus to the cytoplasm, US3 protein is responsible for UL47 localization in the cytoplasm, which was also confirmed in our results ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early events of virus replication, UL47 protein depends on its RNA binding domain incorporated in one of the UL47 NLSs to bind and potentially transport mRNA ( Donnelly et al, 2007 ), or promotes the transition from α to β and γ genes’ mRNA synthesis ( Shu et al, 2013b ), or regulates viral DNA encapsidation and ND10 redistribution in the nucleus ( Zhang et al, 2015 , 2016 ). Afterward, UL47 protein is translocated to the cytoplasm and accumulated in the Golgi apparatus to be allowed virion incorporation during the late stages of infection ( Zhang et al, 2016 , 2019 ), which is important for UL47 as a major structural protein. During the translocation of UL47 protein from the nucleus to the cytoplasm, US3 protein is responsible for UL47 localization in the cytoplasm, which was also confirmed in our results ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, US3 was not the only protein kinase that phosphorylated UL47 protein in DPV, because other Ser sites were also detected to be phosphorylated in our phosphorylation MS analysis ( Table 2 ), such as Ser67, Ser120, Ser144, and Ser283, which were found in the enrichment of UL47 co-transfected with and without US3 expression. Among them, the phosphopeptides containing residues Ser67, Ser120, and Ser144 match the cellular casein kinase 2 (CK2) motif S/T-X-X-D/E ( Joughin et al, 2012 ; Zhang et al, 2015 ), which is universally expressed in almost every subcellular structure ( Zhang et al, 2019 ). Therefore, DPV UL47 protein may be also phosphorylated by CK2 protein, but its function of nucleocytoplasmic-shuttling is not affected by CK2-regulated phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that virions of HSV-1 localize to the Golgi apparatus, which enables virus packaging, envelopment, and trafficking to the cytoplasm ( 25 ). Like HSV-1, Golgi apparatus is the essential site for BoHV-1 packaging into mature virions ( 26 ). Here, Western blotting analysis was performed to detect viral proteins in the isolated Golgi apparatus via using a monoclonal antibody against virus glycoprotein gD and a polyclonal antibody (pAb) against virion-associated proteins, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatitis C virus core protein, which distributes to LDs when expressed alone, binds PML-NBs and inactivates their apoptosis-inducing function (Herzer et al., 2005). Expression of VP8, a tegument protein of bovine herpesvirus 1, targets PML-NBs and increases nuclear LDs (Zhang et al., 2015, 2019). These results suggest that nuclear LDs may be utilized by viruses to evade host defense mechanisms.…”
Section: Function Of Nuclear Ldsmentioning
confidence: 99%